Efeitos de tarefas cognitivas e do aquecimento físico no controle postural de idosas saudáveis fisicamente inativas: estudo controlado, cruzado, randomizado e cego - Battazza, Rafael Ambrósio (2020)
Background: It has been demonstrated that physical warm-up can influence postural control (PC) in young people, however, there is no similar information in older adults. In addition, no studies were found that aimed to investigate the effects of cognitive tasks on PC. Objective: to investigate the effects of cognitive tasks and physical warm-up performed previosly, on PC in healthy and physically inactive older women. Methods: To answer the research questions, two independent studies were carried out: Study 1 – to investigate the effects of cognitive tasks on PC; Study 2 - to investigate the effects of physical warm-up on PC. For both studies a randomized, crossover, controlled and blind fashion was adopted. The PC was evaluated in a force plate in the bipedal upright stance with eyes open. The sway velocity of the center of pressure in the anterior-posterior (CoPap) and medial-lateral (CoPml) directions was considered as the primary outcome. Area and the frequency of sway in the same directions were considered as secondary outcomes. In the study 1, 20 older women were evaluated (age: 65.5 ± 4.59 years, body mass: 69.33 ± 11.71 kg, height: 1.57 ± 0.07 m, BMI: 27.99 ± 4.17 kg/m2) in two conditions: with cognitive tasks (experimental) and without cognitive tasks (control). In experimental condition the PC was evaluated pre- and immediately post and 10 minutes after three cognitive tasks with total duration of seven minutes. The PC in control condition was evaluated at the same moments, but the cognitive tasks were replaced by seven minutes of rest with the volunteers seated on a chair. In the study 2, 18 older women (age: 65.2 ± 4.6 years, body mass: 69.8 ± 12.1 kg, height: 1.57 ± 0.07 m; BMI: 28.2 ± 4.7kg/ m2) were evaluated in two conditions: with physical warm-up (experimental) and without warm-up (control). In the experimental condition the PC was evaluated before, immediately after and 10 minutes after physical warm-up performed on the treadmill with duration of 12 minutes. In the control condition the PC was evaluated at the same moments, but the physical warm-up was replaced by 12 minutes of rest with the volunteers seated on a chair. For both studies, the PC was evaluated three times with duration of 90 seconds. The data were analyzed using the SPSS 20.0 software. A two way analyses de variance (ANOVA) for repeated measures (condition vs moments) was used to verify the influence of cognitive tasks and physical warm-up on PC, with Bonferroni's post hoc test. Results: Study 1: The experimental condition showed significant reductions for the sway velocity of CoPap and CoPml immediately and 10 minutes after the cognitive tasks in relation to the pre-test, and 10 minutes after in relation to the immediately after the cognitive tasks (p<0.05). In the comparison between the groups, lower sway velocity in both directions was observed in the experimental condition in relation to control, immediately and 10 minutes afterwards (CoPap: p=0.005; CoPml p=0.01). The area and frequency of sway did not differ between the evaluated moments and conditions (p> 0.05). Study 2: no significant differences were observed for the moments (pre, immediately post and after 10 minutes) and conditions (warm-up vs control) for velocity, area and frequency of sway in both directions, CoPap and CoPml (p> 0.05). Conclusions: cognitive tasks performed before the evaluation of the PC decrease the sway velocity and this effect can last for 10 minutes. This information is relevant for researchers and clinicians when evaluating the PC. Additionally, our results suggest that the physical warm-up performed on the treadmill does not influence the subsequent PC in healthy older women.